Pengaruh Model Project Based Learning (PjBL) berbasis Pendekatan Saintifik terhadap Keterampilan Proses Sains Peserta Didik pada Materi Animalia - Triyanto, Samuel Agus; Fitdiniyah, Dini; ., Suharsono (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to analyze the effect of implementing the Project-Based Learning (PjBL) model based on a scientific approach on students’ science process skills in the Animalia topic among Grade X MIPA students at SMA Negeri 2 Tasikmalaya during the 2022/2023 academic year. A quasi-experimental method with a matching-only posttest-only control group design was employed. The population consisted of all Grade X MIPA students (280 students across eight classes), with two classes selected purposively as samples: X MIPA 6 as the experimental group (35 students) and X MIPA 8 as the control group (34 students). Data were collected using a science process skills test consisting of 39 multiple-choice questions related to the Animalia topic. The data were analyzed using prerequisite tests (Kolmogorov–Smirnov test: p = 0.200 > 0.05; Levene’s test: p = 0.373 > 0.05) followed by hypothesis testing with an independent samples t-test (Sig. 2-tailed = 0.000 < 0.05). The results indicate that the implementation of the PjBL model based on a scientific approach has a statistically significant effect on students’ science process skills in learning the Animalia topic.